The effects of substituting spray-dried whole egg from egg grading plants for spray-dried plasma protein in phase I diets - Nessmith, W.B. Jr.; Bergstrom, J.R.; Owen, K.Q.; Richert, B.T.; Smith, J.W.II; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A study was conducted to evaluate the effects of replacing spray-dried plasma protein with spray-dried whole egg from egg grading plants on starter pig performance. Up to 50% (3.5% of the diet) of spray-dried plasma protein can be replaced with spraydried whole egg (6% of the diet) without influencing performance of starter pigs.
Keywords: Swine; Starter; Plasma protein; Egg protein